0329 Social Jetlag and Increased BMI: A Population-Based Study Using a Contactless Sleep Measurement Application. (25th May 2022) - Watson, Nathaniel; Gahan, Luke; Raymann, Roy; Gottlieb, Elie
Abstract: Introduction: Social jetlag involves delayed bed and wake times on weekends relative to weekdays. Resulting circadian rhythm disruption, sleep disturbance, and shortened sleep have untoward consequences for human health and performance. Elevated BMI is associated with habitual short sleep and circadian disruption, as seen in shift workers. Studies assessing the relationship between social jetlag and BMI often rely on self-reported sleep patterns, or measure sleep objectively with a worn device for short periods of time. We assessed the relationship between social jetlag and BMI in a novel manner using longitudinal, ecologically valid assessments (measured in subjects typical home environment) using the PSG-validated contactless, sonar-based SleepScore mobile application. Methods: A total of 357 individuals across 130, 120 nights monitored their sleep with the contactless SleepScore mobile application (ages 18-87, mean age, 46.7% females). Social jetlag was determined in a well-established manner by subtracting the mean objective sleep midpoint on weekdays from the mean objective sleep midpoint on weekends. Body mass index (BMI) was self-reported and defined as kg/m2. Chronotype was subjectively assessed with a 5-item question ranging from definitely morning-type to definitely evening-type. Chronotype, age and gender were included in the analysis as confounds. Results: Mean social jetlag was 26.6 min (95% CI 22.2 – 31.0). Linear regression revealed a significant association between social jetlag and BMI (ß=0.025, SE=0.012, p<0.05) after adjustment for age, gender and chronotype. Thus, for every one-minute increase in social jetlag, there was a 0.025 kg/m2 increase in BMI. For expository purposes, a social jetlag of 60 minutes would increase BMI by 1.5 kg/m2. Conclusion: In our population-based sample of individuals using a sonar-based contactless consumer sleep technology to objectively measure sleep we found a positive association between a well-validated measure of social jetlag and BMI, such that increased social jetlag portended increased BMI. This is consistent with previous reports demonstrating the untoward effect of social jetlag on human health and metabolism. The longitudinal and ecologically valid nature of our sleep measurement adds to the veracity of our growing understanding of the problem with social jetlag. Support (If Any): SleepScore Labs